Oligonucleotide biofunctionalization enhances endothelial progenitor cell adhesion on cobalt/chromium stents. Issue 10 (22nd April 2015) - Barsotti, Maria Chiara; Al Kayal, Tamer; Tedeschi, Lorena; Dinucci, Dinuccio; Losi, Paola; Sbrana, Silverio; Briganti, Enrica; Giorgi, Rodorico; Chiellini, Federica; Di Stefano, Rossella; Soldani, Giorgio
Abstract As the endothelium still represents the ideal surface for cardiovascular devices, different endothelialization strategies have been attempted for biocompatibility and nonthrombogenicity enhancement. Since endothelial progenitor cells (EPCs) could accelerate endothelialization, preventing thrombosis and restenosis, the aim of this study was to use oligonucleotides (ONs) to biofunctionalize stents for EPC binding. In order to optimize the functionalization procedure before its application to cobalt–chromium (Co/Cr) stents, discs of the same material were preliminarily used. Surface aminosilanization was assessed by infrared spectroscopy and scanning electron microscopy. A fluorescent endothelial‐specific ON was immobilized on aminosilanized surfaces and its presence was visualized by confocal microscopy. Fluorescent ON binding to porcine blood EPCs was assessed by flow cytometry. Viability assay was performed on EPCs cultured on unmodified, nontargeting ON or specific ON‐coated discs; fluorescent staining of nuclei and F‐actin was then performed on EPCs cultured on unmodified or specific ON‐coated discs and stents. Disc biofunctionalization significantly increased EPC viability as compared to both unmodified and nontargeting ON‐coated surfaces; cell adhesion was also significantly increased. Stents were successfully functionalized with the specific ON, and EPC binding was confirmed by confocal microscopy. In conclusion, stent biofunctionalization for EPC binding was successfully achieved in vitro, suggesting its use to obtain in vivo endothelialization, exploiting the natural regenerative potential of the human body. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3284–3292, 2015.